2017
DOI: 10.6018/eglobal.16.2.235251
|View full text |Cite
|
Sign up to set email alerts
|

Violência contra crianças e adolescentes: características dos casos notificados em um Centro de Referência do Sul do Brasil

Abstract: Objetivo: Conocer la epidemiología de la violencia contra los niños, niñas y adolescentes atendidos en un Centro de Referencia Especializado para la Asistencia Social (CREAS), a partir de los registros de las notificaciones entre enero de 2009 y mayo de 2014.<br /><br />Métodos: Estudio descriptivo y documental, de enfoque cuantitativo que examinó 800 historias clínicas de CREAS. El instrumento de investigación abordó variables sociodemográficas seleccionadas de las víctimas, de los agresores y el … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 11 publications
(16 reference statements)
0
15
0
21
Order By: Relevance
“…8 With the notification, the legal commitment of health professionals is demonstrated, as well as indicating their responsibility in the integral protection of victims of violence, working in conjunction with the safety networks, in the prevention, care and monitoring of cases. 9 In the municipality of Maringá, in 2008, the "Protection Protocol for women, children and adolescents victims of sexual, domestic and intra-family violence" was elaborated with the objective of qualifying the professionals involved in the care of this population, promoting actions of prevention of violence against these groups, as well as identifying cases in the community by hosting and assisting victims and their families. 10 According to this protocol, several entry points for the care and referral of victims of sexual violence are considered, among which the following stand out: Health Services; the Educational System; the Mobile Emergency Care Service (MECS); the Integrated Emergency Response Service (IERS); the Social Assistance Reference Centers (CREAS and CRAS); the Military and Civil Police and the Guardianship Council.…”
Section: Original Articlementioning
confidence: 99%
“…8 With the notification, the legal commitment of health professionals is demonstrated, as well as indicating their responsibility in the integral protection of victims of violence, working in conjunction with the safety networks, in the prevention, care and monitoring of cases. 9 In the municipality of Maringá, in 2008, the "Protection Protocol for women, children and adolescents victims of sexual, domestic and intra-family violence" was elaborated with the objective of qualifying the professionals involved in the care of this population, promoting actions of prevention of violence against these groups, as well as identifying cases in the community by hosting and assisting victims and their families. 10 According to this protocol, several entry points for the care and referral of victims of sexual violence are considered, among which the following stand out: Health Services; the Educational System; the Mobile Emergency Care Service (MECS); the Integrated Emergency Response Service (IERS); the Social Assistance Reference Centers (CREAS and CRAS); the Military and Civil Police and the Guardianship Council.…”
Section: Original Articlementioning
confidence: 99%
“…Também consideram violência maltratar os animais e as plantas. Silva, Lunardi, Lunardi et al 12 , ao pesquisarem o perfil epidemiológico da violência contra crianças e adolescentes em um Centro de Referência Especializado em Assistência Social, identificaram o predomínio do abuso sexual, seguido das violências física e psicológica.…”
Section: Percepções Sobre a Violênciaunclassified
“…A study conducted in Quebec, Canada with 1400 adolescents showed that most were victims of family violence during their lives, of whom 82% were victims of more than one form of victimization (2) . In Brazil, a study conducted in the South region, from medical records of children and adolescents attended at the Reference Center Specialized in Social Assistance (RCSSA), also shows that the main complaints were related to family violence, with the prevalence of sexual, physical and psychological violence (3) . Another national study conducted from anonymous reports of violations of rights against children and adolescents confirms that they experience psychological, physical and sexual violence, also warning of neglect (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Another national study conducted from anonymous reports of violations of rights against children and adolescents confirms that they experience psychological, physical and sexual violence, also warning of neglect (4) . In all studies, the main perpetrators of maltreatment were relatives or other people with close relationship (2)(3)(4) . This is what a Brazilian study conducted with children and adolescents attended in the health service due to the consequences of violence confirms when revealing that more than 70% of the aggressors are considered people from the affective bond, such as father, mother, stepfather, spouse, ex-spouse, boyfriend, ex-boyfriend, brother, and friend/acquaintance.…”
Section: Introductionmentioning
confidence: 99%